Therapeutic Potential of Camel Milk in Type 2 Diabetes Mellitus: A Review - Navneet Kumar, (Asian Journal of Pharmaceutics (AJP), 2025)
Camel milk is known as a superfood due to its high nutritional content; it is high in vitamins and minerals including calcium, iron, magnesium, copper, zinc and potassium. It has various therapeutic properties such as antibacterial, antiviral, and anti-inflammatory, anti-cancer and anti-diabetic properties. Due to its smaller fat globules size, it is easy for digestion. Camel milk has 3 times more Vitamin C than cow’s milk and 10 times higher iron content. Camel milk is considered as hypoglycemic agent due to its blood glucose lowering effect in experimental group with diabetes. Treatment of diabetes by effective alternate therapies is a topic of great concern worldwide. In diabetes the cells may not respond to insulin or defects in insulin secretion by pancreas can cause increase in the blood sugar levels. Camel milk contains insulin-like proteins, that could be beneficial for antidiabetic effect. This milk is considered as hypoglycemic agent as it improves long term glycemic control in diabetic patients. It can also help improve diabetes related risk factors such as liver and kidney damage and cardiovascular complications. As per the evidence more scientific studies are required to validate the effectiveness of camel milk on type 2 diabetes mellitus (T2DM). This review represents scientific studies on favorable effects of camel milk on T2DM.